Interactive Mathematics Activity Books: A Strategy to Boost Students’ Interest and Arithmetic Abilities - Sisi Pitriyana; Iis Juniati Lathiifah (Jurnal Pendidikan Matematika (JPM), 2025)
This research is motivated by the fact that mathematics is still a subject that students consider difficult. The low interest of students in learning leads the low arithmetic ability. This can be caused by school mathematics learning that focuses a lot on practice questions, but is not varied enough. Mathematics learning should use learning media and varied questions. Based on interviews, students' understanding of one material is not enough, they must do an evaluation. Although many students are very effective in learning, there are still many students who have not completed their studies. Although many students are very effective in learning, there are still many students who have not completed their studies. Therefore, other teaching materials are needed to add references in providing exercises. For this reason, this study aims to increase students' interest in learning and also their arithmetic ability. This research method is research and development. The research and development method was chosen with 2 main stages, namely preliminary, which includes preparation and design, then formative evaluation, which includes self-evaluation, expert reviews, one-to-one, small group, and field test. This research was conducted at SD Negeri 19 Pangkalpinang. Participants in this activity were 2nd-grade students, consisting of 32 students. This activity was carried out on November 28, 2024. The activities carried out in this study were the implementation of the use of mathematics activity books developed with the help of Canva, so that with this implementation, students' numeracy skills increased. The results of this activity were an increase in student engagement that was very good, and students were more interested in learning using math activity books. So, it can be concluded that mathematics activity books can improve students' numeracy skills in Mathematics lessons.